Quality Improvement Project: Introducing Pharmacy Input Into Consultant Psychiatry Outpatient Clinics - Mohan Gondhalekar; Ishraq Chowdhury (BJPsych Open)
Aims: This Quality Improvement (QI) Project aimed to enhance the overall level of care received/experienced by patients within the Havering Older Adult Mental Health Team (HOAMHT) through combining the clinical expertise of a Consultant Psychiatrist with the pharmacological acumen of a Specialist Mental Health Pharmacist, within a joint mental health outpatient clinic. Key areas tackled included: medication adherence, faster optimization of psychotropic medications, management of polypharmacy, de-prescription of drugs of dependence, physical health monitoring, and expediting patient discharge from HOAMHT back to the GP.